Expression patterns of the immunomodulatory enzyme arginase 1 in blood, lymph nodes and tumor tissue of early-stage breast cancer patients - de Boniface, Jana (Landes Bioscience, 2012)
Arginase 1 (ARG1) is an important enzyme in amino acid metabolism that also exerts immunoregulatory function. High ARG1 expression, which is associated with cell cycle arrest and functional unresponsiveness in T cells, has been observed after trauma, infections and in cancer patients. We studied ARG1 expression in early-stage breast cancer patients (stage 1, n = 20; stage 2, n = 23) by multi-parametric flow cytometry and immunohistochemistry. Despite a low tumor burden, ARG1 expression was significantly increased in blood-derived myeloid cells of breast cancer patients compared with healthy controls. The ARG1(hi) myeloid population in the blood of cancer patients contained a high frequency of CD14(+) cells and was, therefore, distinct from the granulocytic ARG1(+) population observed in control individuals. Expression of ARG1 in patient blood cells correlated with tumor grade and was significantly reduced after surgical tumor removal. ARG1(+) myeloid cells could also be detected in tumors and tumor-draining lymph nodes, where ARG1 expression levels exceeded those measured in the blood. We conclude that even patients with early-stage breast cancer exhibit tumor-related changes of ARG1 expression. The level of ARG1-mediated immunomodulation at this early stage remains to be determined. However, high ARG1 expression is likely to interfere with antitumor T-cell responses and immunotherapeutic interventions, making ARG1 or its downstream effector interesting therapeutic targets.